Tunisian charitable associations during the first half of the twentieth century (the Islamic Charitable Association as a model) - boutaibi, mohamed (Journal of Social Sciences and Humanities, 2016)
There is no doubt that charitable associations have numerous benefits resulting from their activities, particularly in fostering a sense of unity among members of the nation, strengthening both material and moral solidarity among them, and alleviating social injustice by providing educational assistance and material support to those in need and the underprivileged. They also play a role in enlightening minds, expanding the scope of popular culture, promoting progress, and addressing societal issues and concerns faced by Tunisians during the Protectorate period (1881–1956). For this reason, many charitable associations were established in Tunisia. In this context, our study focuses on the Islamic Charitable Association as one of the charitable models needed by Tunisian society in particular, and Arab-Islamic societies in general, as well as the international community, especially in light of forced displacement and international migration, food insecurity, and the worsening phenomena of poverty and famine worldwide. Accordingly, the main question arises: to what extent was the association able to alleviate the suffering of Tunisian society under French colonial rule? What were the manifestations of its activities and the material means it adopted to achieve its charitable mission during the first half of the twentieth century?